Analisis Literatur Kontemporer tentang Peran Manajemen Keuangan Islam terhadap Penguatan UMKM di Indonesia - Gusnawati Unna; Syahriyah Semaun (Al Rikaz: Jurnal Ekonomi Syariah, 2026)
The conventional financial system, which relies on interest-based instruments and rigid collateral requirements, often creates financial exclusion and liquidity vulnerability for grassroots communities and Micro, Small, and Medium Enterprises (MSMEs). This study aims to construct and analyze the effectiveness of the Islamic Financial System as an alternative architecture for strengthening the economic foundation of society in Indonesia. The research employs a qualitative approach through library research using the Systematic Literature Review (SLR) method. The analysis was conducted on 25 reputable scientific articles published over the last ten years, focusing on the performance of Islamic financial instruments in Indonesia. Data were analyzed using content analysis and thematic analysis of reputable scholarly literature, secondary data, and relevant regulations. The findings reveal that community economic empowerment can be optimally achieved through integrative governance of two main pillars: the Islamic commercial sector (al-tijari), which applies the principle of risk-and-reward sharing, and the social philanthropy sector (al-ijtima'i), which is based on productive Zakat, Infaq, Sadaqah, and Waqf (ZISWAF). The synergy of this dual-pillar financial system, managed under the principles of transparency and accountability, is capable of promoting the structural transformation of underprivileged communities toward sustainable financial independence, thereby realizing distributive justice.